Tools of information and communication technologies in the knowledge management system - I. G. Gorina; N. M. Fomenko (Вестник университета)
This article considers the knowledge management system as an element of the overall management system of the organization along with the processes of corporate culture and corporate education. The implementation of knowledge management system provides an increase in competitiveness, has a favorable effect on the intellectual potential of the organization, human resource management and innovations’ development. The means of information and communication technologies in the knowledge management system, in corporate training and in corporate culture are considered, and the connection between them is outlined. The use of Intranet and Extranet systems in the context of the collection, storage and use of organizational knowledge is analyzed. Corporate training issues from the point of view of increasing the operational efficiency of organizations are touched upon. Trends in the development of corporate culture are outlined, where a special role is played by the formation of a favorable environment for the knowledge transfer. The functioning of corporate education and corporate culture, in the aggregate, can increase the implementation effectiveness of knowledge management system.